2020
DOI: 10.1111/cas.14331
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial V‐like antigen 1 promotes hepatocellular carcinoma growth and metastasis via the ERBB‐PI3K‐AKT pathway

Abstract: The role of epithelial V-like antigen 1 (EVA1) has been well studied in thymic development and homostasis; however, its putative relationship with cancer remains largely unknown. Therefore, here we investigated the role of EVA1 in hepatocellular carcinoma. Interestingly, EVA1 expression was significantly increased in hepatocellular carcinoma (HCC) and was also associated with a poor prognosis and recurrence in HCC patients. Overexpression of EVA1 promoted cell growth, invasion and migration in vitro. Consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…Several studies already reported an association between ERBB3 expression and patients’ outcome in different types of cancer, including lung adenocarcinoma, breast, gastric, and colorectal cancer [ 29 , 30 , 31 ]. Consistently, it has been shown that the ERBB3-PI3K-Akt signaling pathway is directly involved in HCC growth, invasion, and migration [ 32 ]. Furthermore, ERBB3 was identified as a compensatory survival factor that was up-regulated after c-Met inhibition in c-Met + HCC cell line [ 33 ].…”
Section: Discussionmentioning
confidence: 70%
“…Several studies already reported an association between ERBB3 expression and patients’ outcome in different types of cancer, including lung adenocarcinoma, breast, gastric, and colorectal cancer [ 29 , 30 , 31 ]. Consistently, it has been shown that the ERBB3-PI3K-Akt signaling pathway is directly involved in HCC growth, invasion, and migration [ 32 ]. Furthermore, ERBB3 was identified as a compensatory survival factor that was up-regulated after c-Met inhibition in c-Met + HCC cell line [ 33 ].…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, a robust quantitative nomogram plot including the risk score and clinical stage was constructed. GSEA analysis results suggested a potential biological molecular mechanism of risk signature in HCC progression via Wnt ( Dai et al, 2019 ; Hu et al, 2019 ; Huynh et al, 2019 ; Jin et al, 2019 ; Li et al, 2019 ; Tan et al, 2019 ) and ERBB ( Ni et al, 2020 ) signaling pathways and others. Besides, we demonstrated the prognostic risk signature remained a good prognosis predictive accuracy indicator when HCC cases subdivided into subgroups according to clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR inhibition has been shown in studies to inhibit HCC cell survival, migration, and invasion ( Chen et al, 2019 ; Jin et al, 2021 ). The ErBB-PI3K-AKT pathway can promote the growth and spread of hepatocellular carcinoma ( Ni et al, 2020 ). Overexpression of focal adhesion kinase (FAK) occurs frequently in human HCC tissues, and simultaneous overexpression of FAK increases AR expression, which leads to HCC formation in mice ( Shang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%